Chromosomal Localization of Candidate Genes for Fiber Growth and Color in Alpaca (Vicugna pacos) - Mendoza, Mayra N.; Raudsepp, Terje; Alshanbari, Fahad; Gutiérrez, Gustavo; Ponce de León, F. Abel (Frontiers in Genetics, 2019)
The alpaca (Vicugna pacos) is an economically important and cultural signature species in Peru. Thus, molecular genomic information about the genes underlying the traits of interest, such as fiber properties and color, is critical for improved breeding and management schemes. Current knowledge about the alpaca genome, particularly the chromosomal location of such genes of interest is limited and lags far behind other livestock species. The main objective of this work was to localize alpaca candidate genes for fiber growth and color using fluorescence in situ hybridization (FISH). We report the mapping of candidate genes for fiber growth COL1A1, CTNNB1, DAB2IP, KRT15, KRTAP13-1 and TNFSF12 to chromosomes 16, 17, 4, 16, 1 and 16 respectively. Likewise, we report the mapping of candidate genes for fiber color ALX3, NCOA6, SOX9, ZIC1 and ZIC5 to chromosomes 9, 19, 16, 1 and 14 respectively. In addition, since KRT15 clusters with five other keratin genes (KRT31, KRT13, KRT9, KRT14, KRT16) in scaffold 450 (Vic.Pac 2.0.2), the entire gene cluster was assigned to chromosome 16. Similarly, mapping NCOA6 to chromosome 19, anchored scaffold 34 with 8 genes, viz., RALY, EIF2S2, XPOTP1, ASIP, AHCY, ITCH, PIGU and GGT7 to chromosome 19. These results are concordant with known conserved synteny blocks between camelids and humans, cattle and pigs.